Measuring And Analyzing the Impact of Oil Shocks on The Gross Domestic Product in The Kingdom of Saudi Arabia Duration (1970-2020) - et. al., Researcher Ghada Saleh Abboud, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The research aims to measure and analyze the impact of oil shocks on the gross domestic product of the largest oil economy in OPEC, in the short and long terms. The period 1970-2020 covered all the positive and negative oil shocks to the global economy. And by describing a standard model for the oil shock and measuring its impact on the Saudi GDP, and by using the methodology of testing the limits and the slow gaps model ARDEL, after testing the absence of time series from the unit root, as well as analyzing oil shocks through the Impulse Responsible Function. The results support the hypothesis of a positive relationship to oil shocks on GDP in the long term, and thus the two do not move away from each other. And the existence of a short-term positive correlation through the error correction model (ECM). And that the results support the success of the Kingdom of Saudi Arabia and that Saudi Arabia in its efforts to diversify the Saudi economy through the "Saudi Vision 2030" and in reducing the heavy dependence of the oil sector in generating gross domestic product.